3D printing material for tooth manufacturing and tooth restoration and preparation method

By combining ultra-short carbon fiber, zirconium dioxide and photocured glass ionic hydromarinate into dental materials, and making Bletilla extract into particles, the problem of insufficient wear resistance, compressive strength and antibacterial and anti-inflammatory effects of existing dental materials is solved, and higher wear resistance, compressive strength and long-term anti-bacterial and anti-inflammatory effects are achieved.

CN119548412APending Publication Date: 2025-03-04ZHEJIANG CHINESE MEDICAL UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510051452.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-11-28
Filing Date
2025-01-13
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Existing dental materials have shortcomings in wear resistance, compressive strength and antibacterial and anti-inflammatory effects, especially the photocured glass ion hydromarinate has poor wear resistance and is prone to wear, breakage, and fall off. The medicinal effect of Bletilla extract is diluted after mixing with glass ions, reducing its effectiveness.

Method used

Ultra-short carbon fiber, zirconium dioxide and photocured glass ionic hydromensine are used to combine ultrashort carbon fiber, zirconium dioxide and photocured glass ionic hydromensine, and the Bletilla extract is made into particles with a certain hardness and added to 3D printing materials to improve the material's wear resistance, compressive strength and antibacterial and anti-inflammatory effects.

Benefits of technology

It significantly improves the wear resistance and compressive strength of the dental restoration material, so that it can withstand greater bite force, while maintaining good antibacterial, sterilization and anti-inflammatory effects, and extending the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The invention relates to a 3D printing material for tooth manufacturing and tooth restoration and a preparation method thereof. The 3D printing material can be used for tooth restoration and tooth manufacturing and has compound sterilization and anti-inflammation effects. The 3D printing material comprises, by weight, 14%-35% of bletilla striata extract particles, 10%-30% of zirconium dioxide, 5%-20% of short carbon fibers and 50%-70% of glass plasma. The method has the advantages that the problems that in the prior art, compressive strength is low, abrasion resistance is not achieved, abrasion, breakage and falling are prone to occurring due to improper chewing, and cracks are prone to occurring are solved; 2, the release effect of the effective components of the bletilla striata is improved, and the mechanical properties of the prepared teeth, dental crowns and dental prostheses are effectively improved; and thirdly, the antibacterial, sterilizing and anti-inflammatory effects are very good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a 3D printing material for tooth production and tooth repair, which can be used for both tooth repair and tooth production and has compound sterilization and anti-inflammatory effects, and a preparation method thereof, and belongs to the field of 3D printing material manufacturing. Background Art

[0002] CN115813771A, entitled "An Improved Glass Ionomer Based on Bletilla striata", the improved glass ionomer based on Bletilla striata is prepared by mixing glass ionomer and Bletilla striata extract, and the typical preparation method comprises the following steps: preparing appropriate amounts of glass powder and Bletilla striata extract, mixing and screening them, and then mixing them with glass ionomer cement GIC liquid, stirring them, putting them into a mold and letting them stand until solidified, and the standing time needs to be greater than 24 hours. The improved glass ionomer based on Bletilla striata prepared by the present invention has a small dosage and can exert a more significant anti-streptococcus mutans effect than Bletilla striata extract, so that the anti-caries effect is better, and this new type of glass ionomer has a higher compressive mechanical strength, and is applied to the field of dental materials. After tooth filling and repair, it can withstand greater pressure and is less likely to break, thereby further increasing the service life of the glass ionomer. The problems are: first, the wear resistance of light-cured glass ionomer cement is relatively poor, which is not only easy to wear, break and fall off due to improper chewing, but also glass ionomer cement is sensitive to dehydration and easily cracks; second, the bletilla striata extract only improves the effective ingredients of bletilla striata, but cannot change the inherent mechanical properties of bletilla striata; on the contrary, it reduces the mechanical properties of light-cured glass ionomer cement, and the 3% powdered bletilla striata extract combined with light-cured glass ionomer cement is like a star point, so that the efficacy of bletilla striata is diluted by the light-cured glass ionomer cement, thereby reducing the effectiveness of the bletilla striata extract; third, due to the reduction in the mechanical properties of the improved glass ionomer, it cannot meet the requirements of tooth production alone. Summary of the invention

[0003] Design purpose: To avoid the shortcomings of the background technology, and on the basis of the existing background technology, to design a 3D printing material and preparation method for tooth production and tooth restoration that can be used for both tooth restoration and tooth production, and has a compound bactericidal and anti-inflammatory effect.

[0004] Design scheme: In order to achieve the above design objectives. The present invention has the following design schemes: 1. The design of using ultra-short carbon fiber, zirconium dioxide and light-cured glass ionomer cement is one of the design purposes of the present invention. The purpose of this design is: 1) In this field, since the Young's modulus of zirconium dioxide is about 216GPa, it has high hardness, good wear resistance, high strength, is not easy to break, and has a color close to natural teeth and good aesthetics. Therefore, it is suitable for scenes requiring high strength and wear resistance in dental restorations. It is used to make restorations such as teeth and crowns. Its structure is dense, its compressive strength is high, and it can withstand chewing pressure, that is, it can withstand tooth restorations with large bite forces. However, since the density of zirconium dioxide is 5.89g / cm³, if yttrium oxide stabilizer is added, its density reaches 6.05g / cm³, so it is heavy. 2) The carbon content of carbon fiber is over 90%, which is a high-strength and high-modulus fiber. The tensile strength of high-strength and high-modulus fiber is about 2-7GPa, the tensile modulus is about 400GPa, and the density is about 1.5-2.0 grams per cubic centimeter, which is less than 1 / 3 of zirconium dioxide, so it is light in weight. 3) Light-cured glass ionomer cement contains fluoride, which can release fluoride ions to enhance the acid-erosion resistance of teeth. Secondly, the bonding strength of general glass ionomer cement to enamel is 30-50MPa, and the bonding strength to dentin is 20-40MPa, while the bonding strength of light-cured glass ionomer cement to enamel can reach 60MPa, and the bonding strength to dentin can reach 55MPa. If a surface treatment agent is used, the bonding strength to enamel can reach 100MPa, and the bonding strength to dentin can reach 75MPa. In addition, since carboxyl resin monomer components are added to glass ionomer, and primer and adhesive are used during bonding, the bonding strength of single-paste light-cured glass ionomer cement (complex) to enamel can reach 10-17MPa, and the bonding strength to dentin can reach 7-12MPa. At the same time, light-cured glass ionomer cement can provide a variety of different colors of materials to choose from, which can make the color of the restoration more closely match the color of the teeth, achieving the purpose of aesthetic restoration. However, due to the relatively poor wear resistance of light-cured glass ionomer cement, it is not only easy to wear, break, and fall off due to improper chewing, but also glass ionomer cement is sensitive to dehydration and is prone to cracks. This is one of the technical problems that have not yet been solved in this field.

[0005] In order to solve this problem, the present invention found in the course of the subject experiment that the 3D printing material made by compounding ultra-short carbon fiber, zirconium dioxide and glass ionomer to repair or make teeth not only has a wear resistance and strength that is more than 10 times that of the background technology, but also can withstand a bite force that is more than 10 times that of the background technology; and the introduction of ultra-short carbon fiber not only cooperates with zirconium dioxide to further improve the wear resistance and strength of light-cured glass ionomer cement, but also because carbon fiber is suitable for cases with more remaining tooth tissue and smaller tooth defects, it can provide better elasticity and toughness, which completely solves the risk of root splitting, fracture and shedding in the background technology. The comparison parameters are as follows: .

[0006] 2. The design of the Bletilla striata extract microparticles is the second technical feature of the present invention. The purpose of such design is that Bletilla striata contains a variety of chemical components, mainly bibenzyl, phenanthrene, dihydrophenanthrene, 2-isobutyl malic acid glucose oxybenzyl ester and other compounds, which have high medicinal value, can enter the lung, stomach, liver meridian, and have the effects of astringent hemostasis, swelling and tissue regeneration. 1) Astringent hemostasis: Bletilla striata tastes astringent and sticky, the liver is responsible for storing blood, and it enters the liver meridian, which can astringe wounds and stop bleeding. It is often used to treat various bleeding diseases, such as coughing up blood, vomiting blood or bleeding from trauma. 2) Swelling and tissue regeneration: Bletilla striata is bitter and cold in nature, and bitter and cold can relieve blood stasis, clear away heat and detoxify, reduce swelling, and help skin regeneration. It can be used to relieve symptoms such as sores, redness, and long-term unhealing caused by toxic evil invading the skin surface. However, how to give full play to the medicinal properties of Bletilla striata is one of the main research topics of the present invention. A large number of experiments have shown that when Bletilla striata is in powder form and mixed with tooth repair materials to form new improved glass ionomers with Bletilla striata components, the Bletilla striata powder is diluted during the mixing process with the glass ionomer cement, and its medicinal properties are greatly reduced.

[0007] For this reason, the present invention makes the extract of Bletilla striata into Bletilla striata microparticles with a certain hardness, so that when the Bletilla striata microparticles are mixed with other materials to make 3D printing materials for tooth production and tooth repair, only the medicinal properties of the surface of the Bletilla striata microparticles are affected, while the medicinal properties behind the surface remain the same. In this way, the medicinal efficacy of the Bletilla striata microparticles in the 3D printing materials for tooth production and tooth repair will not only not be reduced, but a sustained-release effect will be formed, so that the prepared teeth or repaired teeth have antibacterial, sterilizing and anti-inflammatory effects for a considerable period of time. What is even more unexpected is that the addition of microparticles of Bletilla striata not only does not reduce the compressive strength of the composite substrate of the present invention, but improves it to a certain extent. The reason is: due to the addition of Bletilla striata microparticles, the repaired tooth or the prepared tooth body forms an arched honeycomb structure supported by the Bletilla striata microparticles, and the arched force is greater than the direct force, which is a well-known common sense. Therefore, the addition of Bletilla striata microparticles improves the compressive strength of the repaired tooth or the prepared tooth body, and the comparison parameters are as follows: .

[0008] 3. The design of adding nano silver powder to zirconium dioxide is the third technical feature of the present invention. The purpose of this design is that silver powder is a common Chinese medicinal material with the effects of clearing heat and detoxifying, cooling blood and reducing swelling. It is mainly used to treat symptoms such as high fever due to heat disease, heat toxic sores, wind-heat red eyes, wind-heat toothache, sore throat and sore throat. Its effects are specifically reflected in: 1) Clearing heat and detoxifying: Silver powder contains rich bioactive ingredients, such as flavonoids, phenolic acids, etc. These ingredients have good heat-clearing and detoxifying effects, can effectively inhibit and kill a variety of pathogenic microorganisms, and have good therapeutic effects on symptoms such as high fever due to heat disease, heat toxic sores and sore throats. 2) Blood swelling: The cooling blood ingredients in silver powder can effectively improve blood circulation and reduce blood stasis, thereby achieving the effect of reducing swelling. It has significant therapeutic effects on symptoms such as wind-heat red eyes, wind-heat toothache, sore throat and sore throat. 3) Other effects: In addition to the above two main effects, silver powder is also used to treat some other diseases, such as skin diseases, hemorrhoids, etc.

[0009] The present invention has found in a large number of experiments that when the ratio of the content of nano-silver added to zirconium dioxide reaches 3.0 or more, its antibacterial rate against Streptococcus mutans is greater than 90%, and when the ratio of the content of nano-silver added to zirconium dioxide reaches 3.4% or more, its antibacterial rate against Streptococcus mutans is greater than 95%, and the antibacterial property of the aging group has not been significantly weakened, which fully confirms that the antibacterial agent formed by adding nano-silver zirconium dioxide in the technical solution recorded in claim 1 of the present invention has an excellent antibacterial effect on Streptococcus mutans, and the long-term antibacterial property is sustained and stable. Technical solution 1: A 3D printing material for tooth production and tooth repair, weight percentage: 14% to 35% of Bletilla striata extract particles, 10% to 30% of zirconium dioxide, 5% to 20% of short carbon fibers, and 50% to 70% of glass ionomer.

[0010] Technical Solution 2: A method for preparing 3D printing materials for tooth production and tooth repair, 1) taking short carbon fibers according to a weight ratio, processing the short carbon fibers into ultra-short fibers with a length of less than 1.5 mm, and then placing the ultra-short fibers in a flinging and cutting machine for flinging and cutting, so that incisions are formed on the surface of the ultra-short fibers, forming a spare material A; 2) taking zirconium dioxide according to a weight ratio, and then placing the zirconium dioxide in a grinding machine to manufacture nano-scale materials, forming a spare material B; 3) taking bletilla striata extract according to a weight ratio, and then placing it in a granulator to make bletilla striata particles with a particle size of less than 1 mm, forming a spare material C; 4) spare materials A, spare materials B and spare materials C are placed in a mixer, and then glass ionomer is added to make 3D printing material wires for tooth production and tooth repair.

[0011] Compared with the background technology, the present invention solves the problems of low compressive strength, poor wear resistance, easy wear, breakage, falling off and cracks caused by improper chewing in the background technology; secondly, it not only improves the release effect of the effective ingredients of Bletilla striata, but also effectively improves the mechanical properties of the prepared teeth, crowns and tooth restorations; thirdly, it has very good antibacterial, sterilization and anti-inflammatory effects.

[0012] Specific implementation method (divide into six groups, respectively make 100% of the materials of Bletilla striata, zirconium dioxide, short carbon fiber and glass ionomer, and the content of each is within the respective range) Example 1: A 3D printing material for teeth, tooth production and tooth restoration, with a unit weight of g: Step 1: 14 g of Bletilla striata extract microparticles with a diameter less than 1 mm and greater than 0.1 mm are placed in a granulator, and the Bletilla striata extract microparticles with a diameter less than 1 mm and greater than 0.1 mm are made into a spare material A under existing technical conditions; Step 2: Take 6g of short carbon fiber and place it in a fling cutter composed of multiple cutters to fling and cut it, so that the surface of the ultra-short fiber is cut to obtain spare material B; Step 3: Place the spare material A and the spare material B together with 30g of zirconium dioxide into a mixer and mix them evenly to obtain the spare material C; Step 4: Mix the spare material C and 50 g of light-cured glass ionomer cement evenly to obtain 3D printing materials for teeth and tooth production and tooth restoration; Step 5: Use the 3D printing material for tooth restoration to make 3D tooth production and restoration printing wire through a wire forming machine.

[0013] Example 2: A 3D printing material for teeth, tooth production and tooth restoration, with a unit weight of g: Step 1: 18.2 g of Bletilla striata extract microparticles with a diameter less than 1 mm and greater than 0.1 mm are placed in a granulator, and the Bletilla striata extract microparticles with a diameter less than 1 mm and greater than 0.1 mm are made into a spare material A under the existing technical conditions; Step 2: Take 5g of short carbon fiber and place it in a swing cutter composed of multiple cutters to swing cut so that the surface of the ultra-short fiber is cut to obtain spare material B; Step 3: Place the spare material A and the spare material B together with 26.8g of zirconium dioxide into a mixer and mix them evenly to obtain the spare material C; Step 4: Mix the spare material C and 50 g of light-cured glass ionomer cement evenly to obtain 3D printing materials for teeth and tooth production and tooth restoration; Step 5: Use the 3D printing material for tooth restoration to make 3D tooth production and restoration printing wire through a wire forming machine. Example

[0014] Step 1: 22.4 g of Bletilla striata extract microparticles with a diameter less than 1 mm and greater than 0.1 mm are placed in a granulator, and the Bletilla striata extract microparticles with a diameter less than 1 mm and greater than 0.1 mm are made into a spare material A under the existing technical conditions; Step 2: Take 5g of short carbon fiber and place it in a swing cutter composed of multiple cutters to swing cut so that the surface of the ultra-short fiber is cut to obtain spare material B; Step 3: Place the spare material A and the spare material B together with 22.6 g of zirconium dioxide into a mixer and mix them evenly to obtain the spare material C; Step 4: Mix the spare material C and 50 g of light-cured glass ionomer cement evenly to obtain 3D printing materials for teeth and tooth production and tooth restoration; Step 5: Use the 3D printing material for tooth restoration to make 3D tooth production and restoration printing wire through a wire forming machine. Example

[0015] Step 1: 26.6 g of Bletilla striata extract microparticles with a diameter less than 1 mm and greater than 0.1 mm are placed in a granulator, and the Bletilla striata extract microparticles with a diameter less than 1 mm and greater than 0.1 mm are made into a spare material A under the existing technical conditions; Step 2: Take 5g of short carbon fiber and place it in a swing cutter composed of multiple cutters to swing cut so that the surface of the ultra-short fiber is cut to obtain spare material B; Step 3: Place the spare material A and the spare material B together with 18.4 g of zirconium dioxide into a mixer and mix them evenly to obtain the spare material C; Step 4: Mix the spare material C and 50 g of light-cured glass ionomer cement evenly to obtain 3D printing materials for teeth and tooth production and tooth restoration; Step 5: Use the 3D printing material for tooth restoration to make 3D tooth production and restoration printing wire through a wire forming machine. Example

[0016] Step 1: 30.8 g of Bletilla striata extract microparticles with a diameter less than 1 mm and greater than 0.1 mm are placed in a granulator, and the Bletilla striata extract microparticles with a diameter less than 1 mm and greater than 0.1 mm are made into a spare material A under the existing technical conditions; Step 2: Take 5g of short carbon fiber and place it in a swing cutter composed of multiple cutters to swing cut so that the surface of the ultra-short fiber is cut to obtain spare material B; Step 3: Place the spare material A and the spare material B together with 14.2 g of zirconium dioxide into a mixer and mix them evenly to obtain the spare material C; Step 4: Mix the spare material C and 50 g of light-cured glass ionomer cement evenly to obtain 3D printing materials for teeth and tooth production and tooth restoration; Step 5: Use the 3D printing material for tooth restoration to make 3D tooth production and restoration printing wire through a wire forming machine. Example

[0017] Step 1: 35 g of Bletilla striata extract microparticles with a diameter less than 1 mm and greater than 0.1 mm are placed in a granulator, and the Bletilla striata extract microparticles with a diameter less than 1 mm and greater than 0.1 mm are made into a spare material A under the existing technical conditions; Step 2: Take 5g of short carbon fiber and place it in a swing cutter composed of multiple cutters to swing cut so that the surface of the ultra-short fiber is cut to obtain spare material B; Step 3: Place the spare material A and the spare material B together with 10g of zirconium dioxide into a mixer and mix them evenly to obtain the spare material C; Step 4: Mix the spare material C and 50 g of light-cured glass ionomer cement evenly to obtain 3D printing materials for teeth and tooth production and tooth restoration; Step 5: Use the 3D printing material for tooth restoration to make 3D tooth production and restoration printing wire through a wire forming machine.

[0018] After all experimental samples were placed in distilled water for 24 h, their two ends were fixed on the fixture of the universal material testing machine, and the samples were compressed at a speed of 0.5 mm / min. The load when the sample broke was recorded, and the compressive strength was calculated according to the following formula: Compression strength (MPa) = load at break (N) / cross-sectional area of ​​sample (mm 2 ); - One-way ANOVA and Tukey post hoc test at α = 0.05; F and P are statistical indicators, and N is the sample size.

[0019] Table 1 Comparison of compressive strength (x±s Mpa)

[0020] The experimental results are shown in Table 1. The effects of adding ultra-short carbon fibers, zirconium dioxide, and Bletilla striata extract particles on the compressive strength of glass ionomers show that the compressive strength of Bletilla striata-modified glass ionomers is higher than that of the control group (150±1.63MPa). Therefore, Bletilla striata-modified glass ionomers improve the mechanical properties in terms of compression, and the difference is statistically significant (P<0.05). The compressive strength of Bletilla striata-modified glass ionomers, in which the mass proportion of Bletilla striata extract is 14%, is 7.98 times that of traditional ones, and the mechanical properties in terms of compression are improved the most.

[0021] Material antibacterial performance experiment: Materials and methods: Streptococcus mutans, frosted paper, agar medium Traditional glass ionomer, Bletilla striata extract, Example 1 (the volume of all materials is the same); S. mutans was densely inoculated onto a BHI agar plate using a bacterial loop, cultured at 37°C for 48 hours, and the diameter of the inhibition zone was observed and measured. The diameter of the antibacterial ring is the measured diameter minus the sample diameter. The diameter of the antibacterial ring around each sample was measured three times and the average value was taken.

[0022] Example 7: Based on the above example, the amount of nano silver powder added is 3-3.5%, and a point is selected according to needs, such as: 3%, i.e. 3g; or based on the above example, when the amount of nano silver powder added is 3%, reduce the light-cured glass ionomer cement by 3%.

[0023] Example 8: Based on the above example, the amount of nano silver powder added is 3-3.5%, and a point is selected according to needs, such as: 3.1%, i.e. 3.1g; or based on the above example, when the amount of nano silver powder added is 3.1%, the light-cured glass ionomer cement is reduced by 3.1%.

[0024] Example 9: Based on the above example, the amount of nano silver powder added is 3-3.5%, and a point is selected according to needs, such as: 3.2%, i.e. 3.2g; or based on the above example, when the amount of nano silver powder added is 3.2%, the light-cured glass ionomer cement is reduced by 3.2%.

[0025] Example 10: Based on the above examples, the amount of nano silver powder added is 3-3.5%, such as 3.3%, i.e. 3.3 g; or based on the above examples, when the amount of nano silver powder added is 3.3%, the light-cured glass ionomer cement is reduced by 3.3%.

[0026] Example 11: Based on the above examples, the amount of nano silver powder added is 3-3.5%, such as 3.4%, i.e. 3.4 g; or based on the above examples, when the amount of nano silver powder added is 3.4%, the light-cured glass ionomer cement is reduced by 3.4%.

[0027] Example 12: Based on the above examples, the amount of nano silver powder added is 3-3.5%, such as 3.5%, i.e. 3.5 g; or based on the above examples, when the amount of nano silver powder added is 3.5%, the light-cured glass ionomer cement is reduced by 3.5%.

[0028] Table 2 Comparison of antibacterial ring diameter (x±s mm)

[0029] The experimental results are shown in Table 2. The effect of adding nano-silver powder on the antibacterial properties of glass ionomers shows that the antibacterial properties of glass ionomers modified with Bletilla striata are higher than those of the control group (11.2±0.3 mm). Therefore, the antibacterial properties of glass ionomers modified with Bletilla striata are improved, and the difference is statistically significant (P<0.05). The antibacterial properties of glass ionomers modified with Bletilla striata in which the mass percentage of nano-silver powder is 3.5% are 2.13 times that of traditional ones during preparation, and the antibacterial properties are improved the most.

[0030] Material hardness test: Materials and Methods Example 1, Example 2, Example 3, Example 4, Example 5, Example 6 (the volume of all materials is the same); After all the experimental samples were placed in distilled water for 24 hours, they were placed on the hardness tester, the drill bit was lowered at a speed of 0.5 mm / min, and the hardness of the sample was recorded (Vickers hardness was used in this experiment); - One-way ANOVA and Tukey post hoc test were performed at α = 0.05; - F and P are statistical indicators, and N is the number of samples.

[0031] Table 3 Hardness comparison (x±s HV)

[0032] The experimental results are shown in Table 3. The effects of adding ultra-short carbon fibers, zirconium dioxide, and Bletilla striata extract particles on the hardness of glass ionomers show that the hardness of glass ionomers modified with Bletilla striata is higher than that of the control group (2.16±0.32HV). Therefore, Bletilla striata modified glass ionomers improve the mechanical properties in terms of hardness, and the difference is statistically significant (P<0.05). The hardness of Bletilla striata modified glass ionomers in which the mass proportion of Bletilla striata extract is 14% is 3.85 times that of traditional ones, and the mechanical properties in terms of hardness are improved the most.

[0033] Material bite force test Materials and Methods Example 1, Example 2, Example 3, Example 4, Example 5, Example 6 (the volume of all materials is the same); The above materials were made into jaw pads using 3D printing technology, and all experimental samples were placed in distilled water for 24 hours. After the subjects wore them, the bite force was measured with a bite force tester (Shanghai Analytical Instrument Factory No. 3, MCF-8701), and the measurement was repeated 10 times to calculate the average value; - One-way ANOVA and Tukey post hoc test at α = 0.05; F and P are statistical indicators, and N is the sample size.

[0034] Table 4 Comparison of bite force (x±s N)

[0035] The experimental results are shown in Table 4. The effects of adding ultra-short carbon fiber, zirconium dioxide, and Bletilla striata extract particles on the bite force of glass ionomers show that for the tooth bite force of glass ionomers, the compressive strength of Bletilla striata modified glass ionomers is higher than that of the control group (112±5.28N). Therefore, Bletilla striata modified glass ionomers improve the mechanical properties of bite force, and the difference is statistically significant (P<0.05). The bite force of Bletilla striata modified glass ionomers, in which the mass proportion of Bletilla striata extract is 14%, is 1.28 times that of traditional ones, and the mechanical properties of bite force are improved the most.

[0036] It should be understood that although the above embodiments provide a relatively detailed textual description of the design ideas of the present invention, these textual descriptions are only simple textual descriptions of the design ideas of the present invention, rather than limitations on the design ideas of the present invention. Any combination, addition or modification that does not exceed the design ideas of the present invention shall fall within the protection scope of the present invention.

Claims

1. A 3D printing material for tooth production and tooth restoration, characterized in that Weight percentage: Bletilla striata extract particles 14% to 35%, zirconium dioxide 10% to 30%, short carbon fibers 5% to 20%, and glass ionomer 50% to 70%.

2. The 3D printing material for tooth production and tooth restoration according to claim 1, characterized in that: The length of the carbon fiber is less than 1.50 mm.

3. The 3D printing material for tooth production and tooth restoration according to claim 1, characterized in that: The bletilla striata extract is bletilla striata microparticles.

4. The 3D printing material for tooth production and tooth restoration according to claim 3, characterized in that: The diameter of the Bletilla striata extract particles is less than 1 mm and greater than 0.1 mm.

5. The 3D printing material for tooth production and tooth restoration according to claim 1, characterized in that: Nano silver powder is added into the zirconium dioxide.

6. The 3D printing material for tooth production and tooth restoration according to claim 1, characterized in that: The added amount of the nano silver powder is 3-3.5%.

7. A method for preparing a 3D printing material for tooth production and tooth restoration according to claim 1, characterized in that: 1) Take short carbon fibers according to the weight ratio, process the short carbon fibers into ultra-short fibers with a length of less than 1.5 mm, and then place the ultra-short fibers in a flinging and cutting machine to fling and cut, so that incisions are formed on the surface of the ultra-short fibers to form spare material A; 2) taking zirconium dioxide according to the weight ratio, and then placing the zirconium dioxide into a grinding mill to produce a nano-scale material, constituting a spare material B; 3) taking the Bletilla striata extract according to the weight ratio, and then placing it in a granulator to make Bletilla striata microparticles with a particle size of less than 1 mm, which constitute the spare C material; 4) The spare materials A, B and C are placed in a mixer, and then glass ionomer is added to make 3D printing material filaments for tooth production and tooth restoration.

Citation Information

Patent Citations

  • Improved glass ion based on bletilla striata

    CN115813771A